The Gorgon's severed head : studies in Alcestis, Electra, and Phoenissae - Luschnig, C. A. E. (Mnemosyne, Supplements, 1995)
The Gorgon's Severed Head looks at three plays of Euripides, one early, one middle and one late in his career. Innovations in genre, in the use of the traditional stories, in the representation of women and of gender issues are present at every period. In all three plays characters are depicted creating themselves and each other. Chapter One on Alcestis looks at the artistry of the two main characters and is especially concerned with finding a role for Admetus, the play's most serious problem. The second chapter treats the physical displacement of the myth in Euripides' version of the Electra-Orestes story. A last section approaches the layers of time and space in Phoenissae .